Building National Character through History Lesson - SIRNAYATIN, TITIN ARISKA (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2012)
This study is about building the National Character through History Lesson (Mixed Methods Research Approach of 11th grades’ social class students of SMA Negeri 1 Majalengka). The issues in this study were (1) what is the ideal development pattern or shape of character education according to history teacher? (2) Has the history teaching contributed to the development of students’ character? (3) What are the constraints faced by history teachers in character building through history learning?. As for the purpose of this study were (1) to find the developments’ pattern or shape of character education in the history teaching, (2) to find the contribution of history learning to students character development, and (3) discover the constraints faced by history teachers in developing character through history learning. The method that used in this study was mixed methods and exploratory sequential approach. The results of this study indicated that the ideal developments’ pattern or shape of character education by history teachers is through the development of character-based lesson plann. Every history teaching needs to specify the character to be developed in accordance with contextual material and adapted to the students’ developmental level, varieties learning methods that encourage and motivate students to be better, media and learning resources that are relevant to students’ characteristics, such as varying assessment using alternative evaluation based on character learning assessment, and conduct advance evaluation of the history teaching by conducting classroom action research (CAR) so that it can be ascertained that the history teaching has been conducted optimally. Moreover, the character education development pattern can also be seen from the qualifications and competencies of the history teacher that determine the success of the students’ character development in building the character of the nation. Learning history has a clear contribution to develop the students’ character, although still low. In developing the students’ character through teaching history, some constraints faced by history teachers are (1) the lack of teacher skills in designing history lesson plan (RPP) contained character education, (2) the deficient of utilization of media or learning sources that reinforce the achievement containing character education, (3) lack of teachers’ understanding and skills in developing alternative assessment in the assessment process.